HAK DAN KEWAJIBAN SUAMI ISTRI DALAM PERSPEKTIF AL-QUR’AN : (KAJIAN TEMATIK) - Suhartawan, Budi (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2022)
This paper aims to examine the truth about the rights and obligations of husband and wife listed in the Qur'an. How does the Qur'an regulate and explain the rights and obligations of husband and wife so that it can be a solution in carrying out a harmonious husband and wife relationship. This research is a thematic-based library research. The method used by the author is descriptive analytical method. The primary data source is a verse of the Qur'an which discusses the rights and obligations of husband and wife. The results of this study indicate that the husband's obligations to his wife; give a dowry, provide spiritual zohir, have good intercourse with the wife, protect the wife from things that bring sin, while the wife's obligation to her husband; complementing the husband's shortcomings, being obedient to his husband, following his husband's residence, maintaining self-respect and his husband's property when he is not there, devoting himself to the husband in taking care of his children, and covering the husband's disgrace.